2017
DOI: 10.4269/ajtmh.16-0902
|View full text |Cite
|
Sign up to set email alerts
|

Haiti’s Commitment to Malaria Elimination: Progress in the Face of Challenges, 2010–2016

Abstract: Abstract.Haiti is committed to malaria elimination by 2020. Following a 2010 earthquake and cholera epidemic, Haiti capitalized on investments in its health system to refocus on malaria elimination. Efforts, including expanding diagnostics, ensuring efficacy of standard treatments, building institutional capacity, and strengthening surveillance were undertaken to complement the broad health system strengthening activities. These efforts led to the adoption and scale-up of malaria rapid diagnostic tests as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 26 publications
(23 reference statements)
3
45
0
Order By: Relevance
“…These distinctive characteristics, along with the threat of emerging resistance to chloroquine [ 17 ] and renewed international attention towards shrinking the world malaria map [ 18 ], have led the Haitian and Dominican governments to commit to eliminating malaria by 2020 [ 19 ]. Over the last few years, several malaria prevention and diagnosis measures were adopted by Haiti’s Ministry of Public Health and Population, notably: adoption of rapid diagnostic tests (RDTs), drug-resistance monitoring, addition of primaquine to chloroquine as first-line therapy, establishment of an insectary and insecticide-resistance monitoring, implementation of surveillance sentinel sites, and strengthening of molecular and serological testing capacity at the national public health laboratory [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These distinctive characteristics, along with the threat of emerging resistance to chloroquine [ 17 ] and renewed international attention towards shrinking the world malaria map [ 18 ], have led the Haitian and Dominican governments to commit to eliminating malaria by 2020 [ 19 ]. Over the last few years, several malaria prevention and diagnosis measures were adopted by Haiti’s Ministry of Public Health and Population, notably: adoption of rapid diagnostic tests (RDTs), drug-resistance monitoring, addition of primaquine to chloroquine as first-line therapy, establishment of an insectary and insecticide-resistance monitoring, implementation of surveillance sentinel sites, and strengthening of molecular and serological testing capacity at the national public health laboratory [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because this study demonstrated a substantial gain of additionally detected low-density infections, particularly in low transmission settings, us-qPCR could be crucial for surveillance in elimination settings. Molecular diagnosis is increasingly used to determine presence of infections to guide control efforts [26]. The use of us-qPCR, and thus greater con dence in diagnostic metrics, could reduce the number of samples to be screened before declaring a region malariafree.…”
Section: Discussionmentioning
confidence: 99%
“…Light microscopy is dictated as the gold standard for malaria diagnosis by the Haitian Ministry of Health; however, after allowing the alternative use of rapid diagnostic tests (RDT) in recent years, they are more widely used [3,24,25].…”
Section: Study Sitesmentioning
confidence: 99%
“…In the Americas, Paraguay and Argentina achieved malaria elimination [1,2]. Apart from El Salvador, there remain 18 malaria-endemic countries and territories in the Americas, which includes only 2 in the Caribbean: the Dominican Republic and Haiti, on the sole island of Hispaniola on which malaria elimination is also considered feasible [3]. Plasmodium falciparum is the endemic species, transmission is mainly focal, and the annual incidence was < 1% in Haiti and reached < 0.1% in 2018 whereas < 1000 cases were reported for the Dominican Republic [1,4].…”
Section: Introductionmentioning
confidence: 99%